A novel ZrGeO4 catalyst for degradation of organic dye pollutants at room temperature without light illumination. Issue 3 (2nd July 2020) - Tang, Jianting; Liu, Haoran; Zhao, Caixian; Rao, Tongde; Hu, Lei; Hu, Chuanbo; Zhang, Lei; Li, Tingzhen
ABSTRACT: New catalysts satisfying simultaneously pollutant-removing and energy-saving have great potential in numerous environmental applications. To develop catalysts effective in decomposing organic dye pollutants under the energy-saving conditions of catalytic wet air oxidation (CWAO), herein we synthesized a new ZrGeO4 catalyst. The catalytic performance of the ZrGeO4 sample is superior to the previous CeGeO4 and ZrHIO6 ·4H2 O analogues in degrading rhodamine B (RhB) and methylene blue (MB). After being recycled for 3 times in the degradation experiments, the ZrGeO4 catalyst did not undergo obvious loss in activity and change in chemical composition. The main active species for the dye degradation over ZrGeO4 were also investigated. GRAPHICAL ABSTRACT: UF0001